Robot Building for Beginners - Cook, David. (Apress : Imprint: Apress, 2010)
“I wrote this book because I love building robots. I want you to love building robots, too. It took me a while to learn about many of the tools and parts in amateur robotics. Perhaps by writing about my experiences, I can give you a head start.” —David Cook Robot Building for Beginners, Second Edition is an update of David Cook’s best-selling Robot Building for Beginners. This book continues its aim at teenagers and adults who have an avid interest in science and dream of building household explorers. No formal engineering education is assumed. The robot described and built in this book is battery powered and about the size of a lunchbox. It is autonomous. That is, it isn’t remote controlled. You’ll begin with some tools of the trade, and then work your way through prototyping, robot bodybuilding, and eventually soldering your own circuit boards. By the book’s end, you will have a solid amateur base of understanding so that you can begin creating your own robots to vacuum your house or maybe even rule the world!